Electrolyte leakage and carotenoid content in chickpea leaves in response to infection with Ascochyta rabiei - B.L. JALALI, S.K. KHIRBAT and (Indian Phytopathology, 2002)
The electrolyte leakage and carotenoid content of leaves of chickpea (Ascochyta blight resistant E100Y and susceptible H-208 cultivars) were determined 2, 4, 6, 8 and 10 days after challenge inoculation with two isolates of A. rabiei. There was a significant increase in the activity of electrolytes after inoculation with both the isolates in resistant and susceptible genotypes in comparison with the uninoculated control. However, the increase was more pronounced at 6 and 10 days after inoculation in the resistant genotype, and at 8 to 10 days after inoculation in the susceptible genotype. The electrolyte leakage was higher in the resistant genotype than in the susceptible genotype. The carotenoid content was also significantly greater in both genotypes following inoculation with the 2 isolates of the pathogen. However, the increase was more pronounced in the susceptible genotype 10 days after inoculation. The role of these two factors in disease resistance of chickpea is briefly discussed.